Longitudinal Assessment of Competency Development in Post-Mortem Examination Training for Medical Students - Samantsinghar, Pusparaj; Shrivastava , Dharmsheel (Seminars in Medical Writing and Education, 2023)
Post-mortem examinations were vital in forensic science, helped to determine the cause of death and offered essential insights for medico-legal investigations. Proper training in autopsy procedures was crucial for medical students pursuing careers in forensic pathology. However, little was known about how competency in this area develops over time. Research aims to assess how medical students’ competency in performing post-mortem examinations evolves throughout their training and to identify factors that influence skill development. A total of 183 medical students participated, with their competency evaluated at various stages of training. During assessments, participants demonstrated their technical competence as well as diagnostic abilities and procedural expertise. IBM SPSS software version 29 has been utilized in the research. ANOVA, Chi-square tests and T-tests formed the basis for performance assessment, as these methods revealed periodic performance differences and competency reinforcement variables. Student skills significantly improved due to the training curriculum used during the educational journey. Students achieved notable advancement in the technical capabilities together with improvement in precise medical diagnosis. Education combined with repeated practice developed essential skills significantly as early training focused on distinct abilities compared to later stages of training. Post-mortem examination training programs helped students achieve marked progress in the competence development. Systematic assessment methods proved essential for forensic pathology education, as they helped medical students achieve professional-level skill development, according to the data results.